2015
DOI: 10.1007/s40518-014-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Quantity Impacts of Hydraulic Fracturing

Abstract: The academic literature has lagged both industry and public opinion in measuring and characterizing potential water quantity and quality concerns related to hydraulic fracturing (fracking). However, the science behind fracking's water impacts experienced its own boom during the 2010s. In this paper, we address this critical emerging environmental and energy issue, providing an overview of the current state of knowledge, with a particular focus on academic journal articles that have been published in the past f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…This discussion is based on the results from Scenario 3, Table 6. Range of water demand for HF in the different areas in the shale formations in the United States [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discussion is based on the results from Scenario 3, Table 6. Range of water demand for HF in the different areas in the shale formations in the United States [19].…”
Section: Discussionmentioning
confidence: 99%
“…Water intensity for HF varies on several factors such as depth, type of shale resources, and thickness of each formation. In shale basins in the United States, HF has required between 1 × 10 9 and 28 × 10 9 gallons of water per Quads (gal/Quads) in gas areas, and between 1.5 × 10 9 and 21.7 × 10 9 gal/Quads in tight oil areas [19]. In the Eagle Ford Shale formation in Texas, which extends to Mexico, the average water consumption in the oil and gas shale areas, based on the wells estimated ultimate recovery, is 2.6 × 10 9 and 1.5 × 10 9 gal/Quads [20].…”
Section: Introductionmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License national economies and the social well-being of mankind in many countries (Haggerty et al, 2014;Weber, 2012); oil infrastructure construction which usually include clearing of land, development of roads and the digging of terraces (Brittingham et al, 2014), have often been linked to environmental destruction and degradation. Studies in Tanzania have also shown that the presence of offshore hydrocarbons (Kuwayama et al, 2015) in marine parks of Mafia Island and Mnazi Bay have been linked to notable environmental risks (Souther et al, 2014). Generally, oil and gas production activities have often been associated with negative ecological impacts; including loss of biological diversity (Pelletier and Coltman, 2018) and limited ecological functioning (Copeland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While many of the water quality implications have been explored (e.g., [5], [6], [7], [8]), a better understanding of the potential stress that fracking may cause to water resources at the local or regional scale is still needed [9]. For example, most previous studies that analyze the costs associated with unconventional fuel production do not address the costs (real or hidden) of accounting for the water availability required to perform fracking operations (e.g., [10], [11], [12]). Although some studies have related water-stressed regions with fracking activities [6], [13], [14], [15], only a few studies [16], [17], [18], attempted to quantify the potential impact of water used for fracking on the local and regional water resources.…”
Section: Introductionmentioning
confidence: 99%